Film-forming materials in contemporary formulations of cosmetic products - Pantelić Ivana; Savić Snežana; Milić Jela; Vuleta Gordana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2018)
Film-formers are cosmetic raw materials responsible for generating a film after their application. Recently, a certain expansion of these materials is noted, with numerous alleged functions and effects on skin or its appendages, making them a true example of multifunctional ingredients. CosIng database currently lists 965 ingredients with the recognized film-forming function. This paper offers a review of different types of film-formers as cosmetic raw materials, their properties and possible combinations in cosmetic products for skin, hair or nails. Although film-forming materials increasingly form part of contemporary cosmetic formulations, the paper mentions only the groups of cosmetic products that contain them in larger amounts, such as anti-age cosmetic products (lifting effect), sunscreens (water resistance and SPF/UVA-PF boosting), hair styling products and nail polishes. In line with the increase in their use, the Scientific Committee on Consumer Safety, operating within the European Commission, has announced recent development of scientific opinions on several cosmetic raw materials with film-forming properties.